2020
DOI: 10.31234/osf.io/s83ru
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social and behavioural responses during the COVID-19 pandemic in Bosnia and Herzegovina

Abstract: In this paper we report results from an online study conducted in Bosnia and Herzegovina during the ongoing COVID-19 pandemic (May 2020). The study examined a range of social and behavioural responses by youth from different ethnic backgrounds and across 63 cities (N = 569). More specifically, the study focused on investigating the relationship between threat perceptions, public health behaviours, stress and social cohesion. As expected, results indicate that higher perceptions of threat were related to higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Hence, since memory of traumatic events has been suggested to be at the core of PTSD symptomatology (Kevers et al, 2016), citizens in Bosnia and Herzegovina who experienced the 1992-1995 war may be acutely reminded of their trauma due to exposure to stress-provoking news in the media and events in their surroundings all of which can cause higher stress levels. Regarding the psychological impact of COVID-19 in Bosnia and Herzegovina, previous studies in Bosnian samples have shown that although citizens' stress levels during the COVID-19 pandemic were low-to-moderate, overthinking, change in sleep patterns, and nervousness were frequently reported (Jankovic & Cehajic-Clancy, 2020); and almost one third of the population had depressive symptoms (Šljivo et al, 2020). Moreover, in studies with multicountry samples including community samples from Bosnia and Herzegovina, it has been shown that the pandemic was associated with deterioration of quality of life (Repišti et al, 2020) and worsening of pre-existing psychiatric conditions (Gobbi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, since memory of traumatic events has been suggested to be at the core of PTSD symptomatology (Kevers et al, 2016), citizens in Bosnia and Herzegovina who experienced the 1992-1995 war may be acutely reminded of their trauma due to exposure to stress-provoking news in the media and events in their surroundings all of which can cause higher stress levels. Regarding the psychological impact of COVID-19 in Bosnia and Herzegovina, previous studies in Bosnian samples have shown that although citizens' stress levels during the COVID-19 pandemic were low-to-moderate, overthinking, change in sleep patterns, and nervousness were frequently reported (Jankovic & Cehajic-Clancy, 2020); and almost one third of the population had depressive symptoms (Šljivo et al, 2020). Moreover, in studies with multicountry samples including community samples from Bosnia and Herzegovina, it has been shown that the pandemic was associated with deterioration of quality of life (Repišti et al, 2020) and worsening of pre-existing psychiatric conditions (Gobbi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%